The matrix effect: how agricultural matrices shape forest fragment structure and amphibian composition. (12th February 2017) - Ferrante, Lucas; Baccaro, Fabricio Beggiato; Ferreira, Eric Batista; Sampaio, Maria Fernanda de Oliveira; Santos, Thays; Justino, Rodrigo Cesário; Angulo, Ariadne
Abstract: Aim: Habitat loss and fragmentation are considered the main drivers of species population declines and extinctions in the world. The large‐scale replacement of natural habitats with human‐modified habitats, such as the replacement of forests with agricultural and livestock farming areas, creates a scenario where natural habitat patches are immersed in an inhospitable land use matrix. We sought to evaluate how forest fragments (FFs) are influenced by the different surrounding landscape components, where we assessed how agricultural matrices that differ in structure and seasonality affect the structure of FFs and their amphibian assemblages. Location: Atlantic Forest, Brazil. Methods: Using diverse methods including satellite imagery, historical land use and field data, we evaluated the effects of representative agricultural matrices on the structure of FFs and their amphibian composition, species richness and abundance. Results: Our results suggest that the structure of FFs and amphibian composition, species richness and individual abundance are intimately linked to the type of matrix and its proportion around FFs. The nature of the matrix is more likely to affect species richness, individual abundance and composition of amphibian assemblages than FF size, reducing the species‐area relationship in FFs. There is strong support for the hypothesis that certain agricultural matrices facilitate FF exposure to the elements and a decrease in forest integrity within the fragment, which is reflected in a loss of strict forest inhabitants. Those matrices that allow for a greater exposure of FFs also appear to favour their occupation by habitat generalists. Main conclusions: Surrounding matrices affect the structure and dynamics of forest remnants and should therefore be considered in management plans of severely fragmented landscapes. The influence of the land matrix should be urgently assessed, as it has effects on species occurrences and distribution. This is especially relevant considering the increasing deforestation rates in biodiversity hotspots world‐wide.